(untitled) (Selecciones Matemáticas, 2024)
In this paper, we study oriented surfaces S in R3, called surfaces with quadratic support function (in short QSF-surfaces). We obtain a Weierstrass type representation for the QSF-surfaces which depends on two holomorphic functions. Moreover, classify the QSF-surfaces of rotation. Also, we give some explicit examples of this class of surfaces.